Epidemiological characteristics of nontuberculous mycobacteriosis and bronchiectasis: comparative study using national mortality statistics from 1970 to 2015 in Japan. Issue 1 (20th February 2023) - Morimoto, Kozo; Iwai, Kazuro; Yoshiyama, Takashi; Ito, Masashi; Uesugi, Fumiko; Asakura, Takanori; Osawa, Takeshi; Furuuchi, Koji; Kurashima, Atsuyuki; Fujiwara, Keiji; Hasegawa, Naoki; Tanaka, Yoshiaki; et al.
Background: This study assessed longitudinal national data on mortality due to nontuberculous mycobacteriosis (NTMosis) and bronchiectasis and the association between the two diseases. Methods: We analysed the national death statistics of Japan from 1970 to 2015. The International Classification of Disease (ICD) codes were used to extract the relevant data. Crude mortality, age-adjusted mortality and standardised mortality rates were calculated using vital statistics and the population in 2000. We also identified domestic publications related to NTMosis and bronchiectasis with an internet-based search system. Results: The total number of bronchiectasis-related deaths remained at the same level, which was approximately 1000, for 45 years, although the number of deaths has consistently decreased in males but increased in females since the mid-1990s. A substantial increasing trend in females was also observed for NTMosis in the same period. The age-adjusted mortality data showed an increase in mortality in women due to NTMosis and confirmed the trend in bronchiectasis in women. The patterns in the number of domestic reports showed a recent slight increase in bronchiectasis and a marked increase in NTMosis. Conclusions: The trends in bronchiectasis-related mortality differed by sex. The epidemiological trends in the two diseases were associated, especially in elderly females since the mid-1990s. It is suggested that pulmonary NTMosis without pre-existing bronchiectasis might be a leading cause of postinfectious bronchiectasis in Japan. The epidemiological trends in NTM-related and bronchiectasis (BE)-related mortality are interrelated. Female BE-related deaths increased in the mid-1990s due to the prominent increase in NTMosis. NTMosis might be the leading cause of BE. https://bit.ly/3DTChdL